E-087 Hybrid open and endovascular approach for occipital arteriovenous fistula with complete obliteration: technical note. (22nd July 2019) - Lavie, J; Mathkour, M; Gulotta, P; Vidal, G; Milburn, J; Valle-Giler, E
Abstract : Background: Dural arteriovenous fistulas (DAVFs) are acquired abnormal shunting connexions between the meningeal arteries and dural sinus or cortical veins and are an important cause of intracranial hemorrhage. Lesions with retrograde cortical venous reflux carry a higher risk of bleeding and endovascular embolization is currently the first-line treatment for these lesions. We present a case of DAVF with cortical venous reflux not amenable to conventional transarterial or transvenous endovascular embolization treated with direct surgical access to the occipital artery and Onyx embolization. Method: A 67-year-old man with a history of seizure disorder who presented with a tonic-clonic seizure one month after stopping his antiepileptics. Neurologic examination was unremarkable aside from diminished hearing on the right. The patient presented for neurosurgical evaluation due to imaging findings performed for work-up of his most recent seizure. Non-contrast head CT was unremarkable. CT and MR angiogram were performed, demonstrating prominent cortical veins overlying the right temporal convexity, suspicious for dural AV fistula or arteriovenous malformation. Digital subtraction angiography confirmed a dural AV fistula with arterial supply from the right occipital and middle meningeal arteries and shunting to the transverse sinus with multiple dilated cortical veins, compatible with a Borden 3, Cognard 4 lesion. In addition, there was a type 3 aortic arch with an extremely tortuous right common carotid artery, precluding selective access to the external carotid artery by either transfemoral or transradial approach. Due to the inability to access the right external carotid artery via conventional endovascular approaches, we elected to perform a hybrid procedure with surgical cutdown for direct access to the right occipital artery for Onyx embolization. Result: Using ultrasound guidance, the right occipital artery was tracked over the posterior nuchal line. A linear incision was designed over it and the artery was exposed and catheterized with a short 5F sheath. Vessels loops were used to secure the sheath to the artery. An onyx compatible microcatheter was used to access the nidus of the fistula and under direct fluoroscopy the fistula was embolized. A Post-embolization angiogram from the right occipital artery demonstrated no residual filling of the fistula. The postoperative was unremarkable and follow up angiogram at 6 months shows complete obliteration. Conclusion: A variety of hybrid open and endovascular approaches have been described and the majority describes approaches involve a combination of a craniotomy followed by Onyx or NBCA embolization after direct cannulation of the artery or vein. In this case, we report a combined surgical and endovascular approach for Borden III DAVF that was inaccessible to standard endovascular approaches due to tortuous carotid anatomy via a direct cut-down. Direct cannulation of the occipital artery provided an elegant access to the fistula distal to the tortuous carotid anatomy with minimally invasive surgery without requiring a craniotomy, and a large volume of Onyx was able to be injected via the prominent occipital artery. Direct cannulation of feeding vessels to dural AVF represent a treatment option in patients that are not good candidates for conventional endovascular or open approaches. Disclosures: J. Lavie: None. M. Mathkour: None. P. Gulotta: None. G. Vidal: None. J. Milburn: None. E. Valle-Giler: None.